Job Characteristics and Organizational Justices as Predictors of Employee Engagement - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
The present study seeks to discover the role of job characteristics and organizational justice (procedural, distributive, interpersonal and informational) in predicting employee engagement. Organizations believe that employee engagement is one of the competitive strategies to sustain in the changing business environment. It was clear from the earlier studies that engaged employees offer a key competitive advantage such as increased productivity and reduced attrition percentage. Most of the organizations were interested in measurement of employee engagement levels to know about their employees’ engagement levels, but ignored to pay attention to how to bring up engagement among employees. Therefore, the current research endeavors to identify the right bundle of factors that were responsible for fostering employee engagement. Specifically, the present study selected job characteristics and all the four dimensions of organizational justice based on the fulfillment of psychological condition as stated by Kahn who was the first scholar to provide an in-depth view on personal engagement. Based on the social exchange theory, it was believed that employees will have an obligation to give back their engaged state at their work to their organization when they were bestowed on organizational justice and adequate job dimensions. Quantitative cross sectional survey research design was employed for data collection and analysis for the present study. With an intention to achieve the objective of the study, well structured questionnaires were adopted from various studies. The data were collected from 392 participants belonging to the Information Technology industry. The samples were selected on the basis of location and demographic profiles in order to provide a logical representation of the population. The present study employed (PLS-SEM) partial least squares structural equation modeling techniques to examine the effects of job characteristics and organizational justice (procedural, distributive, interpersonal and informational) on employee engagement. Besides, statistical techniques like Mann Whitney U test and Kruskal-Wallis H test were employed to examine the differences among demographic variables and latent constructs. Visual Pls version 1 and SPSS 23 version software applications were utilized for the purpose. A remarkable outcome of the analysis of the effects of demographic variables on the latent constructs was, experience with the present company had statistically significant differences among all the dimensions of employee engagement and organizational justice. The result of the path analysis was largely supported by the proposed relationship and interpersonal justice had a higher impact on employee engagement than other constructs. Hence, the present study found out that job characteristics and all the forms of organizational justice have a significant impact on employee engagement. From the result of the study it was confirmed that employee engagement can be fostered through job characteristics and implementation fairness in procedural, distributive, interpersonal and informational justice. Finally, the study also provided the limitation, scope and put forward consideration for future research directions.